Nanostructured Electrochemical Sensor Applied to the Electrocoagulation of Arsenite in Wwtp Effluent - Salazar-Gonzalez, R; Sandoval, A; Sandoval, A (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
A sensitive electroanalytical method for the determination of arsenite, based on a heterostructure of aminated multiwalled carbon nanotubes and gold nanoparticles, was applied in an electrocoagulation (EC) treatment for the elimination of arsenite. A sensitive quantitative response was obtained in the determination of As3+ in a secondary effluent from a wastewater treatment plant from Santiago (Chile). The preconcentration stage was optimized through a Central Composite Face design, and the most sensitive peak current was obtained at 200 s and -600 mV of time and accumulation potential, respectively, after a differential pulse voltammetry sweep. Electroanalytical determination was possible in an interval between 42.89 and 170.00 mu g L-1 with a detection limit of 0.39 mu g L-1, obtaining recoveries over 99.1%. The developed method was successfully applied in an electrocoagulation treatment to remove 250 mu g L-1 of arsenite from a polluted effluent in a batch system. Complete arsenite removal was achieved using a steel EC system with a current density of 6.0 mA cm(-2) in less than 3 min of treatment.